협업을 지원하는 분산 페어 프로그래밍 시스템 설계/구현 및 검증 - 노효원; Hyo Won Noh; 박진호; Jin Ho Park; 곽훈성; Hoon Sung Gwak (한국항행학회논문지, 2013)
소프트웨어 개발의 주요 동향 중 하나는 소프트웨어 산업의 세계화에 있다. 글로벌 소프트웨어 개발은 여러 가지 문제에 직면해 있다. 이러한 문제를 해결하기 위해 새로운 소프트웨어 개발 방법론과 프로세스가 필요하다. 최근 XP 동향에서의 개발 단계로 본다면 기존의 개발자와 개발자간의 협업을 위한 도구에서 벗어나 조직 구성원 전체가 협업할 수 있는 시스템이 필요하다. 텍스트 기반의 IDE 플러그인 형태나 단순한 화면공유, 채팅 기능을 제공하는 것이 아닌 구성원 전체가 협업할 수 있는 분산 페어 개발을 지원하는 시스템의 설계하고 개발하였다. The dominant trend in software development is the globalisation of the software industry. This development is faced with diverse problems, which require solution by the adoption of new processes and development techniques. eXtreme Programming (known as XP) is one methodology which is now at the leading edge of software development. This recent trend in XP allows organisation members to cooperate towards the development of new software independently of the existing developers. This is achieved functionally between the members by the development of distributed pair programming, this is not IDE plug-in shape of text, simple screen sharing or chatting function based.